Common diseases alter the physiological age-related blood microRNA profile - Tobias Fehlmann; Benoit Lehallier; Nicholas Schaum; Oliver Hahn; Mustafa Kahraman; Yongping Li; Nadja Grammes; Lars Geffers; Christina Backes; Rudi Balling; Fabian Kern; Rejko Krüger; et al. (Nature Communications, 2020)
Aging is a key risk factor for chronic diseases of the elderly. Here the authors perform large-scale miRNA profiling of blood from individuals of a range of ages and show that common diseases alter the physiological age-related blood microRNA profile.